Diversifying selection between pure-breed and free-breeding dogs inferred from genome-wide SNP analysis - Malgorzata Pilot; Tadeusz Malewski; Andre Moura; Tomasz Grzybowski; Kamil Olenski; Stanislaw Kaminski; Fernanda Ruiz Fadel; Abdulaziz Alagaili; Osama Mohammed; Wieslaw Bogdanowicz (2016)
Domesticated species are often composed of distinct populations differing in the character and strength of artificial and natural selection pressures, providing a valuable model to study adaptation. In contrast to pure-breed dogs that constitute artificially maintained inbred lines, free-ranging dogs are typically free-breeding, i.e. unrestrained in mate choice. Many traits in free-breeding dogs (FBDs) may be under similar natural and sexual selection conditions to wild canids, while relaxation of sexual selection is expected in pure-breed dogs. We used a Bayesian approach with strict false-positive control criteria to identify FST-outlier SNPs between FBDs and either European or East Asian breeds, based on 167,989 autosomal SNPs. By identifying outlier SNPs located within coding genes, we found four candidate genes under diversifying selection shared by these two comparisons. Three of them are associated with the Hedgehog (HH) signalling pathway regulating vertebrate morphogenesis. A comparison between FBDs and East Asian breeds also revealed diversifying selection on BBS6 gene, which was earlier shown to cause snout shortening and dental crowding via disrupted HH signalling. Our results suggest that relaxation of natural and sexual selection in pure-breed dogs as opposed to FBDs could have led to mild changes in regulation of the HH signalling pathway. HH inhibits adhesion and migration of neural crest cells from neural tube, and minor deficits of these cells during embryonic development have been proposed as the underlying cause of “domestication syndrome”. This suggests that the process of breed formation involved the same genetic and developmental pathways as the process of domestication.